BNIP3, a cell pro-apoptotic protein, involved in response to viral infection in orange spotted grouper, Epinephelus coioides. Issue 64 (May 2017) - Cai, Jia; Wei, Shina; Yu, Dapeng; Song, Rui; Lu, Yishan; Wu, Zaohe; Qin, Qiwei; Jian, Jichang
Abstract: BNIP3 is a kind of BH3-only protein that induces both cell death and autophagy. Here, a BNIP3 gene (EcBNIP3) was identified from orange spotted grouper, Epinephelus coioides . EcBNIP3 possessed 236 amino acids residues, contained a conservative BNIP3 domain and a transmembrane region. Besides, EcBNIP3 expressed at a relative high level in heart and spleen. EcBNIP3 transcript was up-regulated after SGIV infection in vitro . Subcellular localization analysis revealed that EcBNIP3 was predominantly localized in the cytoplasm and co-localized with mitochondria. In addition, overexpression EcBNIP3 accelerated SGIV infection induced cell death but inhibited viral genes transcription. Taken together, these results provided new evidence that fish BNIP3 might involved in response to virus infection. Highlights: EcBNIP3 was cloned from orange-spotted grouper, Epinephelus coioides. EcBNIP3 distributed in all examined tissues. EcBNIP3 was up-regulated after SGIV infection in vitro. Over-expression of EcBNIP3 promoted SGIV-induced cell death and decreased viral genes expression in vitro.